From Pop Culture to Political Symbols: Brave Pink, Hero Green, and Resistance Blue in Indonesia - Ayuningtyas, Winda Eka Pahla; Novianti, Sarah; Setiawan, Anang; Arbiyanti, Hartika; Putri, Bilqis Oktaviani (LPPM Institut Pendidikan Nusantara Global, 2026)
In August 2025, Indonesia witnessed one of the largest protest waves in its history, sparked by public anger over elite privilege, detrimental policies, and government inaction. Amid this upheaval, three colors: Brave Pink, Hero Green, and Resistance Blue emerged as a symbolic repertoire that unified diverse demands. This article employs a qualitative case study that integrates semiotic analysis, Foucauldian discourse analysis, and theories of soft power and people power. It asks: How did this color-based symbolic repertoire function to challenge state power and construct a new political reality? The analysis reveals that these colors were not incidental but were consciously deployed to build a counter-discourse. Brave Pink embodied women's civil courage, Hero Green signaled solidarity and collective mourning for the working class, while Resistance Blue revived historical democratic struggle. By synthesizing the attractive force of soft power with the mobilizing energy of people power, this repertoire forged new cross-class political identities and expanded the protest arena into the digital sphere. The study concludes that this phenomenon illustrates how a simple, shared visual language can dismantle official narratives and construct an alternative